Comfort oral route in hospitalized older people: The multidisciplinary team perception (Revista Contexto & Saúde, 2025)
Objective: To analyze the perception of the multidisciplinary team regarding the use of comfort oral feeding in elderly individuals before and after training. Methods: A cross-sectional and descriptive quantitative study was conducted with professionals from the multidisciplinary team of a University Hospital. A questionnaire was administered before and after training on the use of comfort oral feeding. The sample consisted of 21 professionals from different professions. Statistical analysis was performed using Pearson's Chi-Square test (5% significance level). Results: The average age of the sample was 31.86 years, with most participants having one to five years of professional experience and being from the Nursing field. In the association between pre- and post-training responses, only the question related to the authorization of oral feeding for a patient despite aspiration risk showed statistical significance (p=0.003), indicating that the training was an effective tool, as professionals who had previously marked "do not know" in response to the first questionnaire took a clear favorable or unfavorable position. Conclusion: The perception of the multidisciplinary team regarding comfort oral feeding for hospitalized elderly individuals reveals that this topic is still not widely disseminated and lacks consensus among healthcare professionals. There are doubts regarding its applicability in hospital routines. These uncertainties can be resolved through health education strategies tailored to daily workflow realities, such as training sessions utilizing banners.
Keywords: Palliative Care; Deglutition Disorders; Older Adults; Quality of Life; Patient Care Team.